2016
DOI: 10.1055/s-0035-1561617
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic Metamorphosis of Dibenzothiophenes

Abstract: In general, aromatic cores are stable owing to their resonance energies. Different from facile peripheral modifications of aromatic cores, transforming an aromatic core into a different skeleton is ambitious and has attracted only little attention as a general synthetic method. This personal account shows our journey to inventing transformations of dibenzothiophenes into triphenylenes, carbazoles, and spirocyclic diarylfluorenes and to establishing 'aromatic metamorphosis' as a useful and game-changing strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 10 publications
0
25
0
Order By: Relevance
“…Once dithia [8]helicene is synthesized, we would be able to take advantage of our synthetic strategy about endocyclic transformations of thiophene compounds, which we have coined 'aromatic metamorphosis'. 13 According to our previous reports about the transformations of dibenzothiophene S,S-dioxides into carbazoles 14 and uorenes, 15 we expected the synthesis of diaza [8]helicene and the carbon analog from the sulfone being feasible, although one concern would lie in the chirality conversion during the aromatic metamorphosis. Here we report that the asymmetric synthesis of a series of dihetero [8]helicenes has been indeed viable.…”
Section: Introductionmentioning
confidence: 99%
“…Once dithia [8]helicene is synthesized, we would be able to take advantage of our synthetic strategy about endocyclic transformations of thiophene compounds, which we have coined 'aromatic metamorphosis'. 13 According to our previous reports about the transformations of dibenzothiophene S,S-dioxides into carbazoles 14 and uorenes, 15 we expected the synthesis of diaza [8]helicene and the carbon analog from the sulfone being feasible, although one concern would lie in the chirality conversion during the aromatic metamorphosis. Here we report that the asymmetric synthesis of a series of dihetero [8]helicenes has been indeed viable.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that dibenzothiophenes can be converted into a variety of ring systems, such as dibenzosiloles, dibenzophospholes, fluorenes, and carbazoles [ 22 , 23 , 24 , 25 , 26 ]. Transformation to dibenzosiloles and dibenzophospholes involves (1) the generation of 1,1′-dianions via desulfurative dilithiation with lithium metal and (2) the subsequent reaction of the resulting 1,1′-dianions with silicon and phosphorus electrophiles, respectively.…”
Section: Introductionmentioning
confidence: 99%
“… [a] The conversions of 1a were usually >95 % unless otherwise noted. The second intramolecular S N Ar reaction would be the rate‐limiting step, and, according to our previous reports, [17–25] the major by‐product would be the corresponding zwitterionic species shown below, which was difficult to quantify.
…”
Section: Resultsmentioning
confidence: 92%